KRITIK SOSIAL DALAM NASKAH DRAMA KAMPONG KARDUS KARYA GEPENG NUGROHO - Ariani, Mega Fransiska; Qur?ani, Hidayah Budi (Universitas Negeri Surabaya, 2018)
This study aims to reveal the social criticism found in the drama kampung kardus by Gepeng Nugroho. To answer these problems, use the theory of Alan Swingewood with a sociological approach to literature. This research is a type of qualitative research with a descriptive form. Data collection techniques are done by reading the entire drama script. Data analysis was carried out by reading the entire drama script, identifying data, classifying data, analyzing it in descriptive form by using interpreters of researchers, concluding findings, writing reports on research results. The results showed that Gepeng Nugroho presented stories about social criticism in 1) aspects of poverty, 2) aspects of education, and 3) aspects of crime. In the aspect of poverty researchers find a form of poverty in the form of work, the majority of jobs as scavengers are poverty because scavengers are jobs that cannot meet the daily needs of hindup. In the educational aspect the researcher found a form of laziness in trying to improve life, in this aspect the population underestimated the importance of education. In the crime aspect, researchers discovered forms of crime committed by village leaders who took advantage of scavengers through projects to be carried out.